Competency of Islamic Education Teacher to Improve Student Learning Achievement - Mohammad Rasikhul Islam (EDUTEC : Journal of Education And Technology, 2018)
The competency of the teacher can contribute or increase learning achievement can be an active example of inofative criminative and have high integration in school. The purpose of this research is to know the role of the PAI master competence in enhancing student learning achievement. This research uses the method of decriptif with a qualitative approach, data collection techniques using observations, interviews and documentation studies. Research subjects are the principals and teachers of PAI. The results of the study showed: (1). Pedagogic competence, (2). Personality Competencies (3). Social competence and (4). Professional competence.